Peran Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Pulau Morotai Dalam Meningkatkan Kinerja Aparatur Pemerintah Desa - Dominggus, Idhan; Latief, Fandi Hi. (Jurnal Ilmiah Wahana Pendidikan, 2025)
The study aims to determine the extent to which the Role of the Community and Village Empowerment Service of Morotai Island Regency in Improving the Performance of Village Government Apparatus. The research technique is a qualitative method, in this study the data collection process includes observation, interviews, documentation. The results of the study found that the Community and Village Empowerment Service of Morotai Island Regency has carried out performance in accordance with the provisions of performance measurement indicators in improving the performance of village government apparatus. There are various development programs implemented to encourage the performance of village government apparatus. The conclusion of this study is that the Role of the Community and Village Empowerment Service of Morotai Island Regency in Improving the Performance of Village Government Apparatus has not run optimally because there are inhibiting factors in improving the performance of village government apparatus, where most of the human resources of village government apparatus are still high school educated, so what is done by the Community and Village Empowerment Service in improving the performance of village government apparatus has not been well understood.